Peripheral Administration of a Melanocortin 4-Receptor Inverse Agonist Prevents Loss of Lean Body Mass in Tumor-Bearing Mice - Nicholson, Janet R.; Kohler, Götz; Schaerer, Florian; Senn, Claudia; Weyermann, Philipp; Hofbauer, Karl G. (The Journal of pharmacology and experimental therapeutics, 2006)
Cachexia affects many different chronically ill patient populations, including those with cancer. It results in loss of body weight, particularly of lean body mass (LBM), and is estimated to be responsible for over 20% of all cancer-related deaths. Currently, available drugs are ineffective, and new therapies are urgently needed. Melanocortin 4-receptor (MC4-R) blockade has been shown recently to be effective in preventing cancer cachexia in rodent models. In the present study, we have tested a MC4-R blocker, ML00253764 [2-{2-[2-(5-bromo-2-methoxyphenyl)-ethyl]-3-fluorophenyl}-4,5-dihydro-1 H-imidazolium hydrochloride] (Vos et al., 2004), in vitro and in vivo. In membranes of human embryonic kidney 293 cells expressing human MC4-R, ML00253764 displaced [Nle4, d-Phe7]-α-melanocyte-stimulating hormone binding with an IC50 of 0.32 μM. At concentrations above 1 μM, ML00253764 decreased cAMP accumulation (maximal reduction of -20%) indicative of inverse agonist activity. ML00253764 was administered twice daily (15 mg/kg s.c.) for 13 days to C57BL6 mice bearing s.c. Lewis lung carcinoma tumors. Food intake and body weight were measured, and body composition was assessed using magnetic resonance relaxometry. ML00253764 stimulated light-phase food intake relative to vehicle-treated controls (p < 0.05), although no effect was observed on 24-h food intake. During the 21 days of the experiment, the LBM of tumor vehicle-treated mice decreased (p < 0.05). In contrast, the tumor-bearing mice treated with ML00253764 maintained their LBM. These data support the view that MC4-R blockade may be a suitable approach for the treatment of cancer cachexia and that MC4-R inverse agonists may have potential as drug candidates.